Probing the parameters of the intergalactic medium using quasars. Issue 1 (24th March 2022) - Dalton, Tony; Morris, Simon L; Fumagalli, Michele; Gatuzz, Efrain
ABSTRACT: We continue our series of papers on intergalactic medium (IGM) tracers using quasi-stellar objects (QSOs), having examined gamma-ray bursts (GRBs) and blazars in earlier studies. We have estimated the IGM properties of hydrogen column density (NHXIGM ), temperature, and metallicity using XMM–Newton QSO spectra over a large redshift range, with a collisional ionization equilibrium model for the ionized plasma. The NHXIGM parameter results were robust with respect to intrinsic power laws, spectral counts, reflection hump, and soft excess features. There is scope for a luminosity bias given both luminosity and NHXIGM scale with redshift, but we find this unlikely given the consistent IGM parameter results across the other tracer types reviewed. The impact of intervening high-column density absorbers was found to be minimal. The NHXIGM from the QSO sample scales as (1 + z ) 1.5 ± 0.2 . The mean hydrogen density at z = 0 is n 0 = (2.8 ± 0.3) × 10 −7 cm −3, the mean IGM temperature over the full redshift range is log( T /K) =6.5 ± 0.1, and the mean metallicity is [ X /H] = −1.3 ± 0.1( Z ∼ 0.05). Aggregating with our previous GRB and blazar tracers, we conclude that we have provided evidence of the IGM contributing substantially and consistently to the total X-ray absorption seen in the spectra. These results are based on the necessarily simplistic slab model used for the IGM, due to the inability of current X-ray data to constrain the IGM redshift distribution.